Sleep Improvement Effect on Sexual Life Quality Among Rotating Female Shift Workers: A Randomized Controlled Trial. Issue 8 (6th April 2020) - Khastar, Hossein; Mirrezaie, Seyed Mohammad; Chashmi, Nooshin Ahmadian; Jahanfar, Shayesteh
Abstract: Background: Poor sleep quality consequences among shift working nurses are well recognized. Aim: To investigate the impact of sleep improvement on sexual quality of life. Methods: The study was a parallel randomized controlled trial, conducted among 120 female nurses in 2 educational hospitals in the Northeast of Iran, Shahroud. Using random blocks of four, 120 eligible participants were randomly assigned to study groups. Data collecting tools included a demographic data questionnaire, Pittsburgh Sleep Quality Index to assess sleep quality, and the survey of sexual quality of life-female and Sexual Self-Efficacy Questionnaire to evaluate level of sexual quality of life and sexual self-efficacy, respectively. The intervention consisted of 3 weekly sleep intervention sessions that lasted from 90 to 120 minutes. Outcomes: The study's primary and secondary outcomes were sleep quality, and the level of sexual self-efficacy and sexual quality of life, respectively. Results: By 3-month follow-up, the loss to follow-up rate was 5.9%. The mean sleep quality score was 7.61 ± 2.26 in the recruited participants. Following the intervention, the sleep quality score showed statistically significant differences compared to the control group [mean difference (CI 99.98%),  −1.89 (−2.40,  −1.38)]. Participants in the intervention group showed modest increases in both measures; sexual self-efficacy [mean difference (CI 99.98%), 8.82 (6.83, 10.81)] and sexual quality of life [mean difference (CI 99.98%), 19.64 (18.08, 21.20)]. Clinical Implications: These findings suggest that sleep improvement could promote the sexual quality of life among shift working nurses. Strengths & Limitations: Strengths of this study include the use of a validated outcome measure. Focusing the study on female nurses and the small size of the study population are the limitations. Conclusion: Improved sleep showed an impact on sexual quality of life among rotating female shift workers.